Pengaruh Sapta Pesona Terhadap Kepuasan Pengunjung Pantai Lubang Buaya Negeri Morella Kabupaten Maluku Tengah - Julham Nukuhaly; Marie Tahalele; Andrie Ch Salhuteru (Jurnal Administrasi Terapan, 2024)
This research aims to determine: The influence of Sapta Pesona on visitor satisfaction at Morella State Crocodile Hole Beach, Central Maluku Regency. This research was conducted at the Morella State crocodile hole beach, Central Maluku Regency. This research uses quantitative and qualitative approaches. The population in this study were all visitors to the crocodile hole beach tour. The sampling technique uses a purposive sampling method with a sample size of 100 people. The data collection technique uses a questionnaire whose validity and reliability have been tested, and the data analysis technique used is simple linear regression. The research results show that the calculated t value for the Sapta Pesona (X) variable is 7.376 with a t table value of 1.984, which means that the calculated t value is greater than the t table value (7.376>1.984) with a significance value of 0.000 which is smaller than 0.05 or (0.000<0.05 ). Based on these results, it can be concluded that the Sapta Pesona variable partially has a positive and significant effect on the visitor satisfaction variable. Keywords: Sapta Pesona, Visitor Satisfaction.